Combination of Autohemotherapy and Vincristine Sulfate in Treatment of Canine Transmissible Venereal Tumor in Bitches in Mozambique - Chissico Júnior, Fernando; Bambo, Otilia Rafael; Cardoso, José Manuel da Mota; Laisse, Cláudio João Mourão; Gallina, Marina Frazatti; Zadra, Vivian Ferreira; Rahal, Sheila Canevese; Santos, Ivan Felismino Charas dos (Acta Scientiae Veterinariae, 2021)
Background: Canine transmissible venereal tumor (TVT) is a tumor of round cells. Vincristine sulfate is the most effective for TVT. Alternatively, hemotherapy is an alternative therapy that consists of the administration of autologous blood and the positive effects are associated with an immunomodulatory effect. Since chemotherapy has some collateral effects, it is necessary to study another treatment with minimal side effects. In this context, this report case aimed to describe the use of autohemotherapy associated with vincristine sulfate for treating a transmissible venereal tumor in the vulvar mucosa of 7 adult bitches, being the first case report in Mozambique, Africa. Case: Seven adult bitches, median size, were referred to the School Veterinary Hospital, School of Veterinary, Eduardo Mondlane University, Maputo, Mozambique, Africa, with a diagnosis of TVT in the vulvar mucosa. All bitches were treated weekly with autohemotherapy and vincristine sulfate for 21 days. The parameters assessed included clinical and TVT macroscopic examination, complete blood count, serum biochemical examination and urinalysis, and were evaluated 60-min before each treatment. No clinical side effects were identified during the treatments. Color, appearance and tumor size were changed during the treatment period, and all bitches showed complete remission of the tumor 21 days after the beginning of treatment or after the third therapeutic session. The values of the complete blood count, serum biochemical and urinalysis did not demonstrate significant variations throughout the evaluated time-points. The TVT cytopathological classification was lymphocytic (42.9 %), plasmacytic (28.6 %) and lymphoplasmacytic (28.6 %). Discussion: The aims of this report were to describe the combination of autohemotherapy and vincristine sulfate for treating the transmissible venereal tumor located in the vulvar mucosa of adult bitches, through clinical and laboratory evaluation, and was not identified side and significant hematological changes. The novelty of this case report was associated with the use of adult bitches with TVT in the vulvar mucosa. Other authors conducted a similar study however with male dog with TVT identified at the base of the penis. The complete remission of the tumor after 3 applications and the absence of side effects showed the effectiveness of this treatment compared with use of chemotherapy without autohemotherapy. In contrast, dogs diagnosed with TVT and treated with vincristine sulfate showed complete remission after 4 treatment sessions However, the use of autohemotherapy alone for treating extragenital TVT in bitches did not induce complete remission after 6 weekly treatments. Doses and administration of autologous blood and vincristine sulfate were in accordance with the recommendations of the literature, and were determined according to body mass. Other routes of administration through the cephalic vein were also used and showed complete remission after 4 treatments. The decrease in size tumor associated with the changes in appearance and color was associated with regression of the TVT. The connective tissue isolating groups of cells identified in the literature were not confirmed in this report, probably due to the phase of the progression of the tumor. The highest percentage of animals with lymphocytoid TVT was different from the literature, which referred to the predominance of the plasmacytoid pattern. The combination of autohemotherapy and vincristine sulfate every 7 days encouraged complete remission of TVT in the vulvar mucosa of adult median size bitches after 3 sessions.